Impact of H-Index Toward Citations Using Linear Regression on Science and Technology Index - Dihin Muriyatmoko; Lalu Ganda Rady Putra (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Number of Journals in Indonesia is quite a lot and various disciplines. Until March 15, 2018, registered 50,889 online and print ISSN by Indonesian Institute of Science (LIPI). The government through Ministry of Research, Technology, and Higher Education of Republic Indonesia (Kemenristekdikti) set regulated on journal index, that is Science and Technology Index (SINTA) assigned to rank quality content and management divided by six categories called S1 to S6 which of the data is taken from Google Scholar and Scopus. This research applies S1 that these journals are accredited “A” by Kemenristekdikti and or index by Scopus. That’s data is shown ranking by sorted based on h-index and citations. S1 shown that journal which has highest h-index uncertain have highest citations too, even some have zeroes. That’s data on S1 become strange and awkward when compared with S2 to S6 because some value of h-index and citations S1 is lower than S2 to S6. This research focus to find how strong correlation or impact h-index toward citations using linear regression. The test result shows that value of Multiple R = 0.78 indicates the correlative is very close, a value of R Square = 0.61 indicates the impact of h-index toward citations achieve 61% and the rest 39% affected by others factor.